Dispensing of psychotropic drugs in the Brazilian capital city before and during the COVID-19 pandemic (2018–2020) - Escalante Saavedra, Pamela Alejandra; Galato, Dayani; de Souza Silva, Calliandra Maria; Rodrigues da Silva, Izabel Cristina; da Silva, Emília Vitoria (Frontiers in Pharmacology, 2022)
Objective: Evaluate the data on the psychotropic drugs dispensed by private community pharmacies before and during the SARS-CoV-2 pandemic. Methods: This cross-sectional study compared the quarterly and annual consumption of psychotropic drugs per Defined Daily Dose per 1000 inhabitants-day (DHD). Interrupted time series were also constructed to expose changes in the consumption pattern in the periods before and after March 2020. Results: Among the 20 most consumed psychoactive drugs, 12 were antidepressants, for example, escitalopram (DHD 7.996 and 10.626; p < 0.001), and sertraline (DHD 6.321 and 8.484; p < 0.001), in addition to the hypnotic zolpidem (DHD 6.202 and 8.526; p < 0.001). The time series reveals (R2 value) a variation in drug dispensing, in DHD values, during the pandemic. Conclusion: Despite the higher variance, a significant increase is clearly seen in the consumption trends of psychoactive drugs, particularly antidepressants, consistent with the pandemic’s influence on the general population’s mental health.